Highlighting the Best English Teaching Method for Katsina State Secondary Schools: Communicative Versus Traditional - Sani, Ibrahim; Saidu, Abdulhakim (Journal of Languages and Language Teaching, 2024)
This study was undertaken to highlight the best English teaching method in Katsina state secondary schools by comparing communicative method (CLT) against traditional method (GTM) Â to ascertain the best approach for teaching Grammar, vocabulary, written composition, oral composition, and oral English. The study population comprised all 2023/2024 SS2 students of public secondary schools in Katsina State. It deploys experimental design which involved gathering quantitative data from the studentsâ€™ post-tests to assess their mastery of these language skills. In order to analyze the collected data, the researchers utilized the SPSS (IBM Statistical Processor Version 25) for precise and efficient processing, generating various necessary outputs to draw meaningful conclusions. Based on the findings, with the exception of teaching grammar which revealed no significant difference as the p-value was.003 which is below .05, CLT proved to be more impactful compared to traditional method in teaching the other four subjects. To this end, the researchers recommend the full implementation of CLT method at Senior Secondary Schools in Katsina State. Similarly, it is suggested that CLT and GTM should be blended in teaching grammar in order to help students to learn the grammatical structures of English and use them in a meaningful and engaging way.